2011
DOI: 10.1007/s10689-011-9472-8
|View full text |Cite
|
Sign up to set email alerts
|

Acinic cell carcinoma of the retromolar trigone region: expanding the tumor phenotype in Cowden syndrome?

Abstract: Cowden syndrome (CS) is a cancer predisposition syndrome caused by germline mutations in the PTEN tumor suppressor gene. It is associated with an increased risk of thyroid, breast and endometrial cancer but many manifestations can be found in the head and neck region, some of which are pathognomonic. Here we report a 35-year-old male referred by his dentist for evaluation of a lesion located near the retromolar trigone. Comprehensive clinical examination revealed papillomatous skin lesions, macrocephaly and gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…An ACC of the retromolar trigone region was described in a 35-year-old patient with a clinical diagnosis of Cowden disease and a genetic analysis positive for a pathogenic mutation in PTEN [42]. Cowden disease is characterized by the presence of multiple hamartomas, a type of malformation mainly affecting the gastrointestinal tract, and an increased susceptibility to breast, thyroid and endometrial cancers [43].…”
Section: Discussionmentioning
confidence: 99%
“…An ACC of the retromolar trigone region was described in a 35-year-old patient with a clinical diagnosis of Cowden disease and a genetic analysis positive for a pathogenic mutation in PTEN [42]. Cowden disease is characterized by the presence of multiple hamartomas, a type of malformation mainly affecting the gastrointestinal tract, and an increased susceptibility to breast, thyroid and endometrial cancers [43].…”
Section: Discussionmentioning
confidence: 99%
“…3 A revisão dos casos de CCA em glândulas salivares menores nos últimos cinco anos (Tabela 2) mostrou uma maior incidência desses tumores como nódulos sintomáticos principalmente diagnosticados em homens com idade variável de 30 a 78 anos, sendo a mucosa jugal o sítio mais acometido. 3,4,5,6,7,8,9,10,11 Autores N Sexo Idade (Anos)…”
Section: Discussionunclassified
“…2,3,4 O presente trabalho teve como objetivo relatar um caso de CCA originado em glândula salivar menor, onde houve diagnóstico precoce e conduta terapêutica adequada, além de comparar o presente caso com outros relatos de CCA descritos na literatura nos últimos seis anos (2010-2016). [4][5][6][7][8][9][10][11] relato do caso Paciente do sexo feminino, 35 anos de idade, foi encaminhada a uma clínica de Diagnóstico Oral queixando-se de dor espontânea em região esquerda da face. Ao exame clínico nenhum tipo de alteração dentária ou na mucosa oral estava relacionado com a queixa.…”
Section: Introductionunclassified
“…It is associated with an increased risk of thyroid, breast, and endometrial cancer but many manifestations can be found in the head and neck region, and the association of acinic cell carcinoma of the minor salivary gland near the RMT with a PTEN-gene-related disorder has already been described. 7 A rare clear cell carcinoma of the retromolar trigone was also described. 8 Leiomyomas are benign tumors originated on smooth muscle and are more frequent at uterine myometrium, gastrointestinal tract, and skin, appearing as asymptomatic well-defined and slow-growing masses.…”
Section: Cancer Of the Retromolar Trigone: Etiology And Diagnosis Etimentioning
confidence: 99%